Design of wearable and wireless electrical impedance tomography system. (January 2016) - Huang, Ji-Jer; Hung, Yi-Hsuan; Wang, Jhi-Joung; Lin, Bor-Shyh
Abstract: Electrical impedance tomography (EIT) is a non-invasive approach to reconstruct the cross-section impedance image of the body. Many EIT systems and impedance image reconstruction algorithms have been proposed in previous studies. However, most of these EIT systems are bulky to cause the limitation of applications. In this study, a wearable and wireless EIT system is proposed to reconstruct impedance images non-invasively and wirelessly. By microminiaturizing the conventional EIT system, the proposed system can provide the advantages of small volume and wireless transmission to reduce the application limitation of conventional EIT systems. Finally, the phantom experiment is tested to validate the performance of the proposed EIT system. The experimental results show the average BR value of the reconstructed image obtained by the proposed system being 1.3 ± 0.2 and the averaged location error ratio being about 6.27 ± 3.14%. Therefore, the proposed wearable and wireless EIT system can be viewed as a good system prototype and may be applied to more clinical applications in the future.